Mesenteric Panniculitis in A Patient with Dengue Fever (Bangladesh Critical Care Journal, 2023)
Mesenteric panniculitis or sclerosing panniculitis is a chronic nonspecific inflammation of mesentery adipose tissue ofsmall intestine and colon. It can also rarely involve retroperitoneal, pelvic and peripancreatic fat. No specific etiologyhas been found behind this rare disease. It is most commonly associated with abdominal surgery, autoimmune diseaseand malignancy. Here we present a case of a middle-aged man with history of abdominal surgery and he was presentedto us with dengue fever. His hospital course was complicated with sudden, severe abdominal pain with clinical featuresof subacute intestinal obstruction, and mesenteric panniculitis was diagnosed during further evaluation. It was a greatchallenge for us not only to diagnose such a disease of rare spectrum, but also to manage this patient who was alreadysuffering from another agonizing disease, dengue feverBangladesh Crit Care J March 2023; 11 (1): 61-64